2023
DOI: 10.3390/antiox12081565
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Chlorella vulgaris Effectively Enhanced the Intestinal Antioxidant Capacity and Immune Status of Micropterus salmoides

Abstract: An M. salmoides fish meal diet was supplemented with 0 (CHL0, Control), 38 (CHL38), 76 (CHL76), 114 (CHL114), and 152 (CHL152) mg/kg C. vulgaris for 60 days, and their serum and intestinal samples were analyzed. The results showed that the albumin (ALB) and total protein (TP) contents were observably enhanced in the CHL76 group compared with the Control group. The intestinal glutathione (GSH) and glutathione peroxidase (GSH-Px) contents were enhanced significantly in the CHL76 group, while the total antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…On the other hand, the antioxidant activity is attributed to the presence of various chemical compounds, including chlorophyll derivatives, terpenoids, and carotenoids. Previous studies with Cv have demonstrated the antioxidant effects of the microalgae [ 60 , 61 ] and those included in foods [ 62 , 63 ], however, CvG, having lower chlorophyll content due to a mutation, could decrease the antioxidant effect of CV-AN provided by macroalgae with phlorotannin [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the antioxidant activity is attributed to the presence of various chemical compounds, including chlorophyll derivatives, terpenoids, and carotenoids. Previous studies with Cv have demonstrated the antioxidant effects of the microalgae [ 60 , 61 ] and those included in foods [ 62 , 63 ], however, CvG, having lower chlorophyll content due to a mutation, could decrease the antioxidant effect of CV-AN provided by macroalgae with phlorotannin [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chlorella has also been reported to exhibit physiological effects such as immune activation, growth promotion, and improvement of stress ulcers [13] [14] [15]. Since chlorella contains a variety of antioxidants and other nutrients [16] [17], it is speculated that chlorella-containing multicomponent supplements may be useful in reducing atherosclerosis. However, the effect of chlorella intake on atherosclerosis is unknown.…”
Section: Introductionmentioning
confidence: 99%